Learning Pancasila through Play: The Effectiveness of the Garuda Puzzle for Elementary Students - Tri Sumarni; Lutma Ranta Alolinggi (International Journal of Asian Education, 2026)
Understanding the symbols of Pancasila is an essential component of civic education in elementary schools because it helps students develop a sense of national identity and understand the values embodied in Pancasila. However, many first-grade students struggle to recognize and understand Pancasila symbols due to the abstract nature of the concepts and the limited use of engaging instructional media. This study aimed to examine the effectiveness of the Garuda Puzzle in improving students’ understanding of Pancasila symbols. The study employed a quantitative approach, using a pre-experimental, one-group, pre-test–post-test design. The participants were 27 first-grade students from SD Negeri 50 Bulu’datu, Palopo City, selected through purposive sampling. Data were collected through pre-test and post-test assessments consisting of ten multiple-choice questions administered before and after three treatment sessions using the Garuda Puzzle. The data were analyzed using descriptive statistics and a paired-samples t-test in SPSS. The findings revealed a substantial improvement in students’ understanding of Pancasila symbols after the intervention. The mean score increased from 44.07 in the pre-test to 71.48 in the post-test. Furthermore, the paired-samples t-test indicated a statistically significant difference between the pre-test and post-test scores (p < .05), demonstrating that the Garuda Puzzle had a significant positive effect on students’ understanding of Pancasila symbols. These findings suggest that the Garuda Puzzle is an effective and developmentally appropriate instructional medium that promotes active learning and enhances civic education learning outcomes among elementary school students.